2011
DOI: 10.1073/pnas.1013103108
|View full text |Cite
|
Sign up to set email alerts
|

Optical imaging of breast cancer oxyhemoglobin flare correlates with neoadjuvant chemotherapy response one day after starting treatment

Abstract: Approximately 8-20% of breast cancer patients receiving neoadjuvant chemotherapy fail to achieve a measurable response and endure toxic side effects without benefit. Most clinical and imaging measures of response are obtained several weeks after the start of therapy. Here, we report that functional hemodynamic and metabolic information acquired using a noninvasive optical imaging method on the first day after neoadjuvant chemotherapy treatment can discriminate nonresponding from responding patients. Diffuse op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
155
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(166 citation statements)
references
References 58 publications
7
155
1
1
Order By: Relevance
“…Robyler and colleagues (2011) reported that an oxyhemoglobin flare on day 1 correlated with chemotherapy response in patients [25]. However, it is unknown whether the same functional response would be seen with other treatment modalities (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Robyler and colleagues (2011) reported that an oxyhemoglobin flare on day 1 correlated with chemotherapy response in patients [25]. However, it is unknown whether the same functional response would be seen with other treatment modalities (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Here, three FD wavelengths and six CW wavelengths provided coverage in the range of 661 -1064nm. While several studies [20][21][22][23][24] have focused on hemodynamic changes throughout the treatment period, dynamic changes during a single infusion procedure are also of interest. Thus, we adapted the system design to acquire nine FD and CW wavelengths simultaneously, which significantly reduced imaging time.…”
Section: Discussionmentioning
confidence: 99%
“…Relative HbT has been shown to be an indicator of tissue malignancy, widely used to assess changes in tumor physiology during neoadjuvant chemotherapy [22][23][24]. StO 2 may also be an important index for predicting tumor responses, since hypoxic tumors have been found to be more resistant to chemotherapy [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These merits permit anyone, including babies, elderly people, and patients with an implanted electronic device, to be measured in a natural environment. Therefore, it is expected to be an easy-to-use tool for functional neuroimaging [1] and for breast cancer detection or monitoring [2,3].…”
Section: Introductionmentioning
confidence: 99%